THE INFLUENCE OF NET INTEREST MARGIN, BANK SIZE, BANK AGE, NON-PERFORMING LOAN, LDR, AND GCG ON THE RISK OF MISCONDUCT WITH REAL GDP AS A MODERATION: (CASE STUDY OF CONVENTIONAL COMMERCIAL BANKS 2014 - 2021) - Rusdwianto Nugroho, Antonius; Muharam, Harjum (Penerbit Lafadz Jaya, 2023)
Bank and financial institution misconduct is a critical problem because it can be the main cause of losses due to management negligence and carelessness and has the potential to cause losses to investors and disrupt the stability of banks or financial institutions as a whole. The trend of financial misconduct continues to increase, this problem has not yet become the focus of attention by researchers and policy makers, especially in developing countries. This research study aims to analyze the influencenet interest margin, bank size, bank age, non-performing loan, LDR, and GCG on the risk of misconduct with real GDP as a moderator (case study of conventional commercial banks in 2014 - 2021). The research population used all conventional commercial banks under OJK supervision in 2014-2021, totaling 94 banks. The sampling technique is purposive sampling method. From a population of 94 commercial banks that met the sample criteria, there were 60 commercial banks. Overall, 60 x 7 = 420 research data were obtained during 7 years of observation (2014-2021). The research results show net interest marginsignificant positive effect onrisk of misconduct with siq value. 0.000 < 0.05 (H1 accepted). Bank Size has a significant positive effect on the risk of misconduct with the Siq value. equal to 0.000<0.05 (H2 accepted). bank age has a significant positive effect on the risk of misconduct with the Siq value. equal to 0.000<0.05 (H3 is rejected). NPL has a significant positive effect on the risk of misconduct with the Siq value. equal to 0.000<0.05 (H4 accepted). LDR has a significant negative effect on the risk of misconduct with the Siq value. equal to 0.000<0.05 (H5 accepted). GCG has a significant positive effect on the risk of misconduct with the Siq value. equal to 0.000<0.05 (H6 is accepted.). And finally, real GDP can moderate the relationship between LDR and the risk of misconduct and the Siq value. amounting to 0.029 < 0.05 (H7 accepted).